The Impact of Ginger Extract (Zingiber officinale Rosc.) Addition on Overrun Value, Melting Resistance, Viscosity, and Hedonic Ratings in Gelato - Hega Bintang Pratama Putra; Ahmad Ni'matullah Al-Baarri; Fitran Dwi Saputra; Friska Putri Cahyanti; Swastika Dewi (Journal of Applied Food Technology, 2024)
Incorporating ginger into gelato can significantly enhance its physical properties and sensory attributes. Ginger contains bioactive compounds like gingerol, which contribute to its distinctive flavor and health benefits, such as anti-inflammatory and antioxidant properties. Ginger can contribute to a smoother texture by interacting with the fat and protein structures in the gelato as well as can enhance the melting resistance of gelato, making it more stable and enjoyable to consume over a longer period. The addition of ginger provides a refreshing, spicy flavor that can elevate the overall taste profile of gelato. This study analyzed the impact of adding ginger extract at different concentrations on the overrun value, melting resistance, viscosity, and hedonic properties of gelato. A completely randomized design was used, with treatments including 0% (T0), 0.5% (T1), 1% (T2), and 1.5% (T3) ginger extract. Higher concentrations of ginger extract affected all parameters: overrun values ranged from 15.72% to 22.03%, melting resistance from 36.64 to 42.06 minutes, and viscosity from 10.06 to 12.76 dPas. Hedonic testing revealed that panelists preferred gelato with 0.5% ginger extract (T1). In conclusion, adding ginger extract to gelato significantly affects its overrun value, melting resistance, and viscosity, with the 0.5% concentration being most preferred by consumers.